Asymmetry of the Mitochondrial Inner Membrane - Wrona, Lynne (My University, 1982)
The mitochondrial inner membrane is highly selective with regard to permeability to solutes and the movement of a large number of large or charged molecules across it therefore requires specific transport processes provided by specific membrane proteins.
In order to study the spatial arrangement of one such protein the adenine nucleotide translocator protein which transports ADP and ATP across the mitochondrial inner membrane, a number of chemical labelling studies of the mitochondrial inner membrane were carried out.
Mitochondrial inner membrane preparations of normal (mitoplasts) and inverted (submitochondrial particles) config~ration with respect to mitochondria have been isolated and the external phosphatidylethanolamine and proteins modified by 3H isethionyl acetimidate. An upper limit of 40-46% of the total PE in mitoplasts was found to be located in the external monolayer.
Differences in protein labelling patterns of isethionyl acetimidate modified mitochondria and SMP was observed. JAI was found to penetrate the outer membrane but not the inner membrane of intact mitochondria.
A tritiated photoreactive phospholipid, 1 palmitoyl-2-(mdiazirinophenoxynonanoyl) phosphatidylcholine (DAP-PC) was incorporated into mitoplasts and submitochondrial particles symmetrically into both monolayers by sonication and asymmetrically using phospholipid exchange protein isolated from beef heart. Photolysis yielded the translocator as a major crosslinked product in both types of particles and with both methods of incorporation.
It was shown that the adenine nucleotide translocator can be asymmetrically labelled by modification of membrane.particles of opposite orientation by water soluble and membrane soluble probes.
Keywords: mitochondria; inner membrane; asymmetry; biochemistry